2005
DOI: 10.1152/ajpheart.00129.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic catecholamine trophic activity contributes to flow-mediated arterial remodeling

Abstract: Stimulation of alpha1-adrenoceptors (ARs) induces proliferation, hypertrophy, and migration of vascular smooth muscle cells and adventitial fibroblasts in cell and organ culture. In vivo studies have confirmed this direct trophic action and found that endogenous catecholamines contribute to neointimal formation and wall hypertrophy induced by mechanical injury. In murine carotid artery, these effects are mediated by alpha 1B-ARs, whereas alpha 1D-ARs mediate contraction and alpha 1A-ARs are not expressed. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
5
34
0
Order By: Relevance
“…These results are consistent with morphological changes detected in media of PA with hypertension. Reported increase in catecholamines-mediated trophic effect (19) and activation of Rho kinase (42) could be the mechanisms responsible for flow-induced vascular smooth muscle hypertrophy, proliferation, and increased reactivity to vasoconstrictors.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with morphological changes detected in media of PA with hypertension. Reported increase in catecholamines-mediated trophic effect (19) and activation of Rho kinase (42) could be the mechanisms responsible for flow-induced vascular smooth muscle hypertrophy, proliferation, and increased reactivity to vasoconstrictors.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cell (VSMC) proliferation is central to the development of vascular diseases, such as restenosis and atherosclerosis. In addition to the fact that prolonged elevation of plasma catecholamines is a risk factor for vascular diseases, recent reports have shown that catecholamines directly induce hypertrophy of the arterial wall by stimulation of ␣ 1 -adrenoceptors (7,10). Catecholamines in cell and organ culture induce dose-dependent proliferation of VSMCs, and the trophic effect is dependent on the production of reactive oxygen species (5).…”
mentioning
confidence: 99%
“…They show that eutrophic (collagen deposition and fibrosis) and hypertrophic (proliferation and migration of smooth muscle cells and of adventitial fibroblasts) remodelling characterizes the damages caused by catecholamines on the vascular wall (1,(4)(5)(6)(7)(8)(9). These observations have also been indirectly confirmed by using a-adrenoceptor antagonists (9)(10)(11)(12)(13) and by experiments in animals submitted to local or systemic sympathetic denervation (14).…”
Section: Discussionmentioning
confidence: 82%
“…This direct trophic effect of catecholamines, mediated by a-adrenoceptors, concerns an increase in extracellular matrix, with consequent wall fibrosis and eutrophic remodelling. Moreover, in animal models employing balloon injury of the carotid or aorta, an exacerbation of this action may be observed with proliferation, hypertrophy and migration of smooth muscle cells and adventitial fibroblasts, leading to hypertrophic remodelling (1,(4)(5)(6)(7)(8)(9). The direct influence of sympathetic neurotransmitters on vascular wall structure has been supported by studies using a-adrenoceptor antagonists that showed a reduction in proliferation of vascular wall cells and in neointimal growth after vascular injury (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 97%